PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN: DENGAN VARIABEL MEDIASI KEPUASAN PELANGGAN - Adika Daniswara; Susilo Toto Rahardjo (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the influence of product quality and brand image on customer loyalty with the role of customer satisfaction as a mediating variable on the millennial generation object that uses Nike sports shoes in Semarang. The number of samples used in this study were 130 respondents who were customers aged between 19-29, used Nike shoes for 1 year, or had purchased Nike sports shoes more than once. This study uses the Structural Equation Model (SEM) analysis method with Partial Least Square (PLS) as a data processing tool. The results of this study indicate that product quality and brand image and customer satisfaction have a positive and significant impact on customer loyalty.